"A Sensitive Non-destructive Method for Detection of Document Frauds using Thermal Ink". Issue 5 (2nd September 2016) - Chayal, Vivekkumar Mangilal; Handa, Deepak R.; Singh, Jeet; Menon, Shobhana K.
Abstract : Ink analysis in forensic document examination is a great challenge today. Number of formulations of inks are available. Out of them some tricky ink formulations are routinely used to commit financial crimes related to cheques, will, deed, bills, contracts and other documents. Thermal Ink is one of the formulations which are used in frauds due to its unique characteristic that it disappears on application of heat above a specific temperature. Disappeared writings in thermal inks are not visible to naked eye. This disappeared ink on documents is not visible even with instruments under 0–300 nm UV range, under IR, transmitted lights, oblique lights, and high resolution magnification. Investigation of such types of cases/ documents have become a challenge due to paucity of research and literature. Here, we deciphered this type of ink on different papers and articles with the help of VSC-6000/HS. The main aim of this research work is to develop simple, rapid, sensitive, eco-friendly, portable, economically viable, and non-destructive method to retrive original disappeared writings of thermal ink. The research in such field will be directly beneficial to society as well as law and enforcement agencies which give additional motivation to do research for questioned document.